Substance misuse in personality disorder and schizophrenia: findings and clinical implications from a high secure hospital. Issue 3 (14th August 2017) - Cappai, Alessandra; Wells, Jodie; Tapp, James; Perkins, Derek; Manners, Anna; Ferrito, Martha; Gupta, Nitin; Das, Mrigendra
Abstract : Purpose: Substance misuse (SMU) is widely prevalent in mentally disordered offenders and is linked with violence and offending behaviour. There is however, a scarcity of literature dedicated to investigating SMU and its clinical correlates in relation to patients detained within high secure hospital settings. The purpose of this paper is to investigate the extent and severity of SMU and corresponding treatment needs in patients with a primary diagnosis of personality disorder (PD) in comparison with mental illness (MI) in a high secure hospital. Design/methodology/approach: The responsible clinicians of all patients ( n =240) detained in a high secure hospital were asked to record information using a SMU screening questionnaire over a ten-month period. Details requested included substance type, history of past use and assessment and treatment needs. Data were recorded and then analysed: descriptive statistics were conducted to report historical use of substances, cross tabulations and χ 2 analysis explored the relationship between SMU and treatment status and diagnosis and offending behaviour and a means comparison analysis was employed to explore length of stay and treatment of SMU. Findings: A total of 230 questionnaires were returned (95 per cent of the patient population). A history of SMU was reported in 88.6 per cent of the sample, with alcohol and cannabis misuse being the most prevalent. At least one substance had been abused by 74.3 per cent of the sample. In two-thirds of the sample, SMU was linked with the onset of mental health problems and symptom exacerbation, including violence. Interestingly, patients with a diagnosis of MI as compared with PD were more likely to have used substances (93.3 per cent compared to 81.9 per cent) and were more likely to need treatment for SMU (64.3 per cent compared to 36.8 per cent). In those with an MI diagnosis, SMU was more likely to be linked with violence and index offence (74.3 per cent compared to 59.0 per cent). Practical implications: SMU is significantly prevalent in high risk mentally disordered offenders and linked to onset of mental health problems and offending. Patients with schizophrenia have a higher prevalence of SMU than PD and are likely to be more in need of treatment. Violence and offending are more likely to be related to SMU in schizophrenia than in PD. Originality/value: This study substantiates existing evidence that SMU contributes to mental health problems and criminogenic behaviour. Furthermore, the study reports new findings that characterize differences of the relationship of SMU to offending in schizophrenia and PD in forensic psychiatric patients presenting to a high secure hospital.